Dynamics of Consumer Adoption of Financial Innovation: The Case of ATM Cards - Yang, Botao; Ching, Andrew T. (Management Science, 2014)
We develop a structural consumer life-cycle model to investigate consumers' adoption and usage decisions of ATM cards. If consumers are forward-looking with a known discount factor, our framework can control for the heterogeneous life span faced by consumers of different ages, and hence measure adoption costs more accurately. Moreover, our framework can recover the monetary value of total adoption costs. To estimate our model, we use an Italian panel data set, which contains information on consumers' adoption decisions for ATM cards, and their cash withdrawal patterns before and after adoption. Our results suggest that one could significantly overestimate adoption costs for the elderly when ignoring their shorter life span. Our policy experiments show that a sign-up bonus targeted to the elderly could be much more effective if implemented as a limited-time offer rather than a permanent offer. Interestingly, if the sign-up bonus is permanent, younger consumers may strategically postpone adoption. This paper was accepted by Pradeep Chintagunta, marketing.